Measurement, correlation of the solubility and solution thermodynamics of 2-cyanoguanidine in (methanol + water) binary solvent systems from T = (283.15 to 343.15) K. (October 2015) - Zhang, Ning; Chen, Jia; Zhao, Haipeng; Shen, Wei; Zhang, Xiaorui; Ren, Yongsheng
Graphical abstract: Experimental and correlated solubility data of 2-cyanoguanidine in (water + methanol) solutions. wt is the mass fraction of methanol in the (water + methanol) mixed solvents: ■, wt  = 0.10;, wt  = 0.20; ▽, wt  = 0.30; ☆, wt  = 0.40; □, wt  = 0.50; ○, wt  = 0.60. The dotted lines are values correlated by the modified Apelblat equation, the solid lines are values correlated by the λh equation. Highlights: Solubility data of DCD in binary mixed solvent was measured at T  = (283.15 to 343.15) K. Method we used is demonstrated feasible by comparing with literature data. Obtained data were correlated by three models. Δ Hd, Δ Sd, and Δ Gd were calculated. Abstract: The solubility of 2-cyanoguanidine in binary solvent mixtures (water + methanol) were experimentally measured from T  = (283.15 to 343.15) K by the static method. The mass fraction of methanol wt is 0.100, 0.200, 0.300, 0.400, 0.500, and 0.600. The experimental results show that values obtained increased with temperature increasing from (283.15 to 343.15) K. Good agreement was found between the experiments and calculations by the modified Apelblat equation, fifth-order polynomial equation and semi-empirical Buchowski–Ksiazczak λh equation. Our experiment values were proven to give best agreement with the modified Apelblat equation. The dissolution enthalpy Δdis H (24119.2 to 38593.9 J · mol −1 ), the dissolution entropy Δdis S (48.4083 to 90.7083 J · mol −1  · K −1 ) and the molar Gibbs free energy Δdis G (7507.9 to 12909.8 J · mol −1 ) were calculated on the basis of the modified Apelblat equation analysis. The solubility and dissolution properties of 2-cyanoguanidine in (water + methanol) binary solvent mixtures obtained in this paper will provide essential support for 2-cyanoguanidine industrial design and further theoretical studies.